The Effect of the Utrujah Method on the Quality of Qur'an Reading at MA Nurul Iman NW Keruak: Pengaruh Metode Utrujah terhadap Kualitas Baca Alquran di MA Nurul Iman NW Keruak - Saprudin Efendi (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This study aims to investigate the influence of the Utrujah Method on the Quality of Qur'an Reading at MA Nurul Iman NW Keruak. The study utilizes a quasi-experimental design (Quasi Experimental Design), specifically the Pretest Posttest Control-Group design. The participants were divided into two groups: the experimental group, which applied the Utrujah method, and the control group, which did not. Prior to the intervention, both groups underwent a pre-test to assess their ability to read the Quran. Afterward, the experimental group received an intervention using the Utrujah method, while the control group continued with the usual learning method. A post-test was conducted after the intervention to compare the differences in the quality of Quran reading between the two groups. The results showed that the students who received the intervention using the Utrujah method experienced a more significant improvement in the quality of their Quran reading compared to the control group. The students in the experimental group demonstrated more fluent and accurate reading of the Quran after the intervention